Regulating Together: Emotion Dysregulation Group Treatment for ASD Youth and Their Caregivers - Shaffer, Rebecca C.; Schmitt, Lauren M.; Reisinger, Debra L.; Coffman, Marika; Horn, Paul; Goodwin, Matthew S.; Mazefsky, Carla; Randall, Shelley; Erickson, Craig (Journal of autism and developmental disorders, 2023)
Individuals with autism spectrum disorder (ASD) experience behavioral and emotional symptoms hypothesized to arise from emotion dysregulation (ED), difficulty modulating emotional experience, expression, and intensity in an acceptable and contextually appropriate manner. We developed Regulating Together (RT)—an intensive-outpatient, caregiver-assisted group program to meet the ASD + ED intervention critical need. A within-subjects trial was conducted (5-week-control lead-in period, 5-week-treatment, and 5-and 10-weeks-post-treatment follow-ups). Forty-four youth with ASD + ED (25 8–12, 19 13–18 yr-olds, 88% male, mean FSIQ of 96) participated. Improvements were found in reactivity, emotion regulation knowledge, and flexibility post-treatment and 10-weeks post-treatment. A reduction in inpatient hospitalization rates by 16% from the 12 months pre-RT to 12 months post-RT was observed. RT shows promise to reduce ED in ASD.